Neuron‐Inspired Steiner Tree Networks for 3D Low‐Density Metastructures (Adv. Sci. 19/2021). Issue 19 (8th October 2021) - Yu, Haoyi; Zhang, Qiming; Cumming, Benjamin P.; Goi, Elena; Cole, Jared H.; Luan, Haitao; Chen, Xi; Gu, Min
Abstract : Neuron‐Inspired Steiner Tree Networks In article number 2100141 by Min Gu and co‐workers, neuron‐inspired Steiner tree networks are proposed and studied as a new method to create low‐density metamaterials, where novel mechanical properties and photonic topological quasiparticles can be discovered. The Steiner tree networks not only demonstrate a twist‐induced mechanical property enhancement, but also host an exotic photonic Fermion resulting from accidental degeneracy.